Utilization E-Commerce for Business Virgin Coconut Oil Nagrak Village, Sumedang Regency - Fauzobihi, Fauzobihi; Adji Wiyono, Bagoes; Lelisa, Widya (Abdi Masyarakat, 2024)
-Commerce is a way to market a product using technology. Small and Medium Enterprises is an entrepreneurial activity to increase employment, increase community income, and encourage economic growth. Virgin Coconut Oil is a coconut-based business product that is processed into hygienic oil and has many benefits. In this era of technology utilization, many businesses have the potential to advance but are constrained because they are still stuttering with increasingly sophisticated technology. The purpose of the research conducted was to determine and analyze the use of E-Commerce in the Virgin Coconut Oil business in Nagrak Village, Buahdua District, Sumedang Regency. The method used in this research is qualitative research. The techniques used in data collection are interview techniques, observation, and documentation. With a strategy to increase the competitiveness of Virgin Coconut Oil SMEs through the use of E-Commerce-based marketing technology and good branding. It is hoped that the research conducted can bring development to SMEs Virgin Coconut Oil in Nagrak Village can make a positive contribution in advancing the competitiveness of SMEs.